Roman historiography : an introduction to its basic aspects and development - Mehl, Andreas (Chichester, West Sussex : Wiley-Blackwell, 2011)
'Roman historiography : an introduction to its basic aspects and development presents a comprehensive introduction to the development of Roman historical writings in the ancient world. Andreas Mehl traces the arc of ancient historical writing about Rome from its origins with the authors of clan history and fragmentary annalists to the writings of Byzantine scholar Procopius, the last major historian of the ancient world. Rooting his survey in the context of its Greek predecessors, and within the broader frame Roman literature and society, Mehl discusses every historical writer of significance in the ancient Roman era and provides much more than simple biographical detail. Also considered are essential themes such as genre, teleology, the idea of Rome, and exemplary moral conduct. By paying scrupulous attention to political context and religious developments throughout the ancient world, Mehl reveals the evolution and interpenetration of both pagan and Christian historiography. This title offers a wealth of illuminating insights into the origins and development of the crucial historical writings of the living witnesses to the greatest empire the world has ever known'--Provided by publisher.
The importance of ancient historiography and the purpose of this book -- Ancient literature and Roman historiography -- The Formation and Establishment of Tradition in the Ruling Class of the Early and Middle Roman Republic -- Early Roman historiography : self-justification and memory in earlier annalistic writing -- The historiography of Rome between the fronts of the civil wars -- Augustan Rome, Roman Empire, and other peoples and kingdoms -- Imperial history and the history of emperors : imperial history as the history of emperors -- Roman history and universal history between classical religion ('paganism') and Christianity -- Some basic principles of ancient historical thought -- Chronological table.
'Originally published in German under the title R$1'Xl(Bische Geschichtsschreibung ... c2001, W. Kohlhammer, Stuttgart'--T.p. verso.s
Includes bibliographical references and index.
Keywords: Historiography -- Rome -- History; Historians -- Rome -- History; Rome -- History -- Sources; Literature and society -- Rome -- History; Latin literature -- History and criticism; Rome -- Historiography